Effectiveness of Tafakur Prayer Spiritual Therapy on Psychological, Spiritual Well-Being, and Pain In Cancer Patients: A Randomized Trial - Priyanto, Priyanto; Susilo, Eko; Aini, Faridah; Ariani, Yulia Eka; Jannah, Luluk Nur (Chakra Brahmanda Lentera Institute, 2026)
Background: Despite growing evidence supporting spiritual interventions in cancer care, limited randomized controlled trials have examined the effectiveness of the culturally adapted Tafakur Prayer Spiritual Therapy (TPST). Therefore, this study aimed to evaluate its effectiveness on psychological well-being, spiritual well-being, and pain among hospitalized cancer patients. Methods: A single-masked randomized controlled trial, strictly guided by the CONSORT framework, was conducted. Forty-two hospitalized cancer patients were successfully recruited via purposive sampling and randomly assigned to either a four-day TPST intervention group or a standard-care control group using block permutation. Allocation concealment was ensured. Baseline characteristics were homogeneous. The independent variable was the intervention, and the dependent variables were measured using the Psychological Well-Being Index, the Spiritual Well-Being Scale, and the Brief Pain Inventory. Data were analyzed using independent and paired t-tests with statistical software. Results: Psychological well-being improved significantly in the intervention group compared with controls, demonstrating notable clinical significance for patients (Mean Difference=9.4, 95% CI=0.70; 18.10, Cohen's d=0.67, p=0.035). Spiritual well-being also showed a significant increase (Mean Difference=13.7, 95% CI=1.64; 25.76, Cohen's d=0.71, p=0.027). Furthermore, pain intensity decreased significantly, successfully shifting these patients to a lower pain category (Mean Difference = -9.3, 95% CI = -15.63 to -2.97, Cohen's d = 0.92, p = 0.005). Conclusion: The culturally structured TPST significantly enhances holistic patient outcomes and alters the subjective pain experience. It should be routinely integrated into standard holistic oncology nursing protocols. Further multicenter randomized controlled trials with larger samples are needed to confirm the long-term effectiveness of this intervention across diverse hospital settings.